Commit 2d4b582e authored by Niels Möller's avatar Niels Möller
Browse files

Fix comment on the ecc_add_ehh formulas.

parent f8870f78
...@@ -55,25 +55,25 @@ ecc_add_ehh (const struct ecc_curve *ecc, ...@@ -55,25 +55,25 @@ ecc_add_ehh (const struct ecc_curve *ecc,
#define z3 (r + 2*ecc->p.size) #define z3 (r + 2*ecc->p.size)
/* Formulas (from djb, /* Formulas (from djb,
http://www.hyperelliptic.org/EFD/g1p/auto-edwards-projective.html#doubling-dbl-2007-bl): http://www.hyperelliptic.org/EFD/g1p/auto-edwards-projective.html#addition-add-2007-bl):
Computation Operation Live variables Computation Operation Live variables
C = x1*x2 mul C C = x1*x2 mul C
D = y1*y2 mul C, D D = y1*y2 mul C, D
T = (x1+y1)(x2+y2) - C - D C, D, T T = (x1+y1)(x2+y2) - C - D, mul C, D, T
E = b*C*D 2 mul C, E, T (Replace C <-- D - C) E = b*C*D 2 mul C, E, T (Replace C <-- D - C)
A = z1*z2 mul A, C, E, T A = z1*z2 mul A, C, E, T
B = A^2 sqr A, B, C, E, T B = A^2 sqr A, B, C, E, T
F = B - E A, B, C, E, F, T F = B - E A, B, C, E, F, T
G = B + E A, C, F, G, T G = B + E A, C, F, G, T
x3 = A*F*T 3 mul A, C, G x3 = A*F*T 2 mul A, C, G
y3 = A*G*(D-C) 2 mul F, G y3 = A*G*(D-C) 2 mul F, G
z3 = F*G mul z3 = F*G mul
But when working with the twist curve, we need to the factor But when working with the twist curve, we have to negate the
x1*x2. We need to switch sign in y3 expressions, and swap F and factor C = x1*x2. We change subtract to add in the y3
G. expression, and swap F and G.
*/ */
#define C scratch #define C scratch
#define D (scratch + ecc->p.size) #define D (scratch + ecc->p.size)
......
Markdown is supported
0% or .
You are about to add 0 people to the discussion. Proceed with caution.
Finish editing this message first!
Please register or to comment